Comparative analysis of immune cell subsets in peripheral blood from patients with periodontal disease and healthy controls. (21st October 2018) - Cheng, W.‐C.; Saleh, F.; Abuaisha Karim, B.; Hughes, F. J.; Taams, L. S.
Summary: Periodontitis is a chronic inflammatory disease caused by the colonization of teeth by the bacterial plaque biofilm and the resultant host immune responses in adjacent periodontal tissues. Disease severity can vary dramatically between patients with periodontitis, with some subjects displaying inflammation without bony destruction (gingivitis), while others experience chronic progressive or rapidly aggressive gingival connective tissue damage and bone loss. To determine whether peripheral immune dysregulation is associated with periodontitis, we performed extensive analysis of immune cell subsets in peripheral blood from patients with chronic or aggressive periodontitis versus periodontally healthy control subjects. Peripheral blood mononuclear cells (PBMC) from patients with chronic periodontitis or aggressive periodontitis and from periodontally healthy controls were analysed by 8–10‐colour flow cytometry for the frequencies of various lymphocyte subsets, including interleukin (IL)‐17‐, interferon (IFN)‐γ‐, tumour necrosis factor (TNF)‐α‐ and IL‐10‐producing cells, and the frequencies and phenotype of monocytes. Cytokine levels in serum from the different groups were determined by Luminex assay. We found no significant differences in the frequencies of major immune cell populations [CD4 + T cells, CD8 + T cells, γδ T cells, CD4 + CD45RO + CD25 + CD127 low regulatory T cells (Tregs ), CD19 + B cells, CD14 + monocytes] or of cytokine‐producing T cells, or in the phenotype of CD14 + monocytes in peripheral blood from these patient cohorts. Additionally, no significant differences were observed in serum levels of prototypical inflammatory cytokines. These results suggest that the local gingival inflammatory response is not reflected by obvious changes in major blood immune cell subset frequencies. Abstract : To determine whether peripheral immune dysregulation is associated with periodontitis, we performed extensive analysis of immune cell subsets in peripheral blood from patients with chronic or aggressive periodontitis vs. periodontally healthy control subjects. We found no significant differences in peripheral blood frequencies of major immune cell populations (CD4+ T cells, CD8+ T cells, gd T cells, CD4+CD45RO+CD25+CD127low regulatory T cells (Tregs), CD19+ B cells, CD14+ monocytes), cytokine producing T cells (IL‐17, IFNg, TNFa or IL‐10+), in the phenotype of CD14+ monocytes, or in serum cytokine levels in periodontitis patient cohorts compared to healthy controls. Our results indicate that the local gingival inflammatory response is not reflected by obvious changes in major blood immune cell subset frequencies.